Enhanced Synaptic Connectivity in the Dentate Gyrus during Epileptiform Activity: Network Simulation. (4th February 2013) - França, Keite Lira de Almeida; Guimarães de Almeida, Antônio-Carlos; Infantosi, Antonio Fernando Catelli; Duarte, Mario Antônio; da Silveira, Gilcélio Amaral; Scorza, Fulvio Alexandre; Arida, Ricardo Mario; Cavalheiro, Esper Abrão; Rodrigues, Antônio Márcio
Abstract : Structural rearrangement of the dentate gyrus has been described as the underlying cause of many types of epilepsies, particularly temporal lobe epilepsy. It is said to occur when aberrant connections are established in the damaged hippocampus, as described in human epilepsy and experimental models. Computer modelling of the dentate gyrus circuitry and the corresponding structural changes has been used to understand how abnormal mossy fibre sprouting can subserve seizure generation observed in experimental models when epileptogenesis is induced by status epilepticus. The model follows the McCulloch-Pitts formalism including the representation of the nonsynaptic mechanisms. The neuronal network comprised granule cells, mossy cells, and interneurons. The compensation theory and the Hebbian and anti-Hebbian rules were used to describe the structural rearrangement including the effects of the nonsynaptic mechanisms on the neuronal activity. The simulations were based on neuroanatomic data and on the connectivity pattern between the cells represented. The results suggest that there is a joint action of the compensation theory and Hebbian rules during the inflammatory process that accompanies the status epilepticus. The structural rearrangement simulated for the dentate gyrus circuitry promotes speculation about the formation of the abnormal mossy fiber sprouting and its role in epileptic seizures.